2011
DOI: 10.1002/micr.20961
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vasopressors on outcomes in head and neck free tissue transfer

Abstract: Intraoperative vasopressors are used routinely in free tissue transfer for the reconstruction of head and neck defects. The use of intraoperative vasopressors does not appear to adversely affect free tissue transfer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 10 publications
3
71
2
Order By: Relevance
“…Preoperative hemoglobin values below 11 g/ dl are associated with an increased length of stay 3b Ideal anesthetic agent unclear; consider sevoflurane Sevoflurane may have protective effects on the endothelium in the context of ischemia-reperfusion injury [13][14][15][16] and may promote vascular healing 17 Sevoflurane superior to propofol with regard to its effects on the capillary filtration coefficient 18 2b Use supplemental epidural anesthesia for lower extremity free tissue transfer Epidural supplementation of general anesthesia correlated with improved flap survival and lower rate of microvascular complications compared with general anesthesia alone 19 1b Implement sympathetic blockade for microsurgery involving the digits Axillary brachial plexus blockade correlated with increased perfusion in replanted digits 20,21 Fluids 2b Maintain crystalloid administration between 3.5-and 6 ml/kg/hr in the 24-hr perioperative period Crystalloid administration >130 ml/kg/day (>5.4 ml/kg/hr) associated with increased major medical complications 22 Extremes of crystalloid infusion associated with increased complications 23 2b Crystalloid administration should not exceed 7 liters intraoperatively Administration of >7 liters of crystalloid during surgery associated with major medical complications and flap complications 24 2b Consider hemoglobin/hematocrit during patient selection Significantly increased risk for flap failure with hematocrit <30%, hemoglobin <10 g/dl 25 2b Restrict blood transfusions to patients with hemoglobin <7 g/dl or who are clinically symptomatic Intraoperative blood transfusion associated with length of surgery, intraoperative arterial thrombosis, major surgical/medical complications 26 Increased risk for cancer recurrence and increased mortality in patients with oral/oropharyngeal squamous cell carcinoma receiving 3 or more units of blood perioperatively 27 Vasodilators 4 Consider topical, low-dose lidocaine to treat persistent vasospasm Application of 4% topical lidocaine during and after surgery improved blood flow in patients with persistent vasospasm 28 Vasopressors 2b Use vasopressors when indicated for hypotension; they do not significantly increase flap failure or complication rates Vasopressor administration did not affect the rates of reoperation, complete flap loss, partial flap loss, or fat necrosis in microsurgical breast reconstruction 29 Vasopressor administration did not affect flap failure rate or complications in head and neck reconstruction 30,31 Vasopressor administration did not affect flap failure rate or complications in upper and lower extremity reconstruction 32 Cumulative dosage and timing of vasopressor administration are not correlated with adverse outcomes 29,33 1b Consider norepinephrine and dobutamine for hypotension following free tissue transfer In a comparison of norepinephrine, dobutamine, epinephrine, and dopexamine administered following free tissue transfer, free flap skin blood flow increased in a dose-dependent manner with norepinephrine and dobutamine, with maximal improvements occurring with norepinephrine; dopexamine and epinephrine decreased flap blood flow 34,35 Dobutamine significantly improved both mean and maximum blood flow through the arterial anastomosis in patients during head and neck reconstructive surgery 36 Altho...…”
Section: Blood Transfusionmentioning
confidence: 98%
See 1 more Smart Citation
“…Preoperative hemoglobin values below 11 g/ dl are associated with an increased length of stay 3b Ideal anesthetic agent unclear; consider sevoflurane Sevoflurane may have protective effects on the endothelium in the context of ischemia-reperfusion injury [13][14][15][16] and may promote vascular healing 17 Sevoflurane superior to propofol with regard to its effects on the capillary filtration coefficient 18 2b Use supplemental epidural anesthesia for lower extremity free tissue transfer Epidural supplementation of general anesthesia correlated with improved flap survival and lower rate of microvascular complications compared with general anesthesia alone 19 1b Implement sympathetic blockade for microsurgery involving the digits Axillary brachial plexus blockade correlated with increased perfusion in replanted digits 20,21 Fluids 2b Maintain crystalloid administration between 3.5-and 6 ml/kg/hr in the 24-hr perioperative period Crystalloid administration >130 ml/kg/day (>5.4 ml/kg/hr) associated with increased major medical complications 22 Extremes of crystalloid infusion associated with increased complications 23 2b Crystalloid administration should not exceed 7 liters intraoperatively Administration of >7 liters of crystalloid during surgery associated with major medical complications and flap complications 24 2b Consider hemoglobin/hematocrit during patient selection Significantly increased risk for flap failure with hematocrit <30%, hemoglobin <10 g/dl 25 2b Restrict blood transfusions to patients with hemoglobin <7 g/dl or who are clinically symptomatic Intraoperative blood transfusion associated with length of surgery, intraoperative arterial thrombosis, major surgical/medical complications 26 Increased risk for cancer recurrence and increased mortality in patients with oral/oropharyngeal squamous cell carcinoma receiving 3 or more units of blood perioperatively 27 Vasodilators 4 Consider topical, low-dose lidocaine to treat persistent vasospasm Application of 4% topical lidocaine during and after surgery improved blood flow in patients with persistent vasospasm 28 Vasopressors 2b Use vasopressors when indicated for hypotension; they do not significantly increase flap failure or complication rates Vasopressor administration did not affect the rates of reoperation, complete flap loss, partial flap loss, or fat necrosis in microsurgical breast reconstruction 29 Vasopressor administration did not affect flap failure rate or complications in head and neck reconstruction 30,31 Vasopressor administration did not affect flap failure rate or complications in upper and lower extremity reconstruction 32 Cumulative dosage and timing of vasopressor administration are not correlated with adverse outcomes 29,33 1b Consider norepinephrine and dobutamine for hypotension following free tissue transfer In a comparison of norepinephrine, dobutamine, epinephrine, and dopexamine administered following free tissue transfer, free flap skin blood flow increased in a dose-dependent manner with norepinephrine and dobutamine, with maximal improvements occurring with norepinephrine; dopexamine and epinephrine decreased flap blood flow 34,35 Dobutamine significantly improved both mean and maximum blood flow through the arterial anastomosis in patients during head and neck reconstructive surgery 36 Altho...…”
Section: Blood Transfusionmentioning
confidence: 98%
“…[29][30][31]33,73 Animal studies have demonstrated an attenuated response to norepinephrine and phenylephrine following surgical sympathectomy. 91 Following vasopressor administration, cutaneous microcirculation actually increased in an amount proportional to the change in mean arterial pressure in postsympathectomy tissue, whereas flow in normal tissue was reduced.…”
Section: Vasopressorsmentioning
confidence: 99%
“…Various studies have reported head and neck flap failure and necrosis rates, from 2.2% to 23% for total flap failure and from 1.4% to 13% for partial flap failure. 4,5 In a surgical field such as the head and neck, where flap failure can lead to catastrophic complications, minimizing flap failure, maximizing viable tissues for inset and coverage of vital structures, and shortening intraoperative time while decreasing the need for operative take-backs are of critical importance for the surgeon and the patient.…”
mentioning
confidence: 99%
“…Moreover, recent studies have also failed to demonstrate a definite relationship between intraoperative vasopressor and free flap complications. 26 In our study, patients in the PAS group had 3-and 14-fold increases in incidence of emergent re-exploration and total flap failure respectively, compared with those in the NPAS group. Thus, PAS should be prevented before a patient regains consciousness, rather than treated after it happens, to decrease flap compromise and potential cardiac risk.…”
Section: Discussionmentioning
confidence: 75%